2014
DOI: 10.1371/journal.pmed.1001590
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of Malaria Rapid Diagnostic Tests and Artemisinin-Based Combination Therapy: Challenges and Perspectives in Sub-Saharan Africa

Abstract: Guido Bastiaens and colleagues describe barriers to achieving scale-up and appropriate use of rapid diagnostic tests and artemisinin-based combination therapy for malaria in sub-Saharan Africa. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 46 publications
4
89
0
Order By: Relevance
“…In this study, all the Malawi [30], found that prescribing anti-malaria drugs to only patients that tested positive after parasitological examination of the blood reduced the total number of anti-malaria medicine prescriptions; and by extension the quantity of anti-malaria drugs consumed in a community. Furthermore, introduction of mRDTs in places where malaria diagnosis was usually through presumptive method, demonstrated significant reduction in over prescription of anti-malaria drugs [31]. One would have thought that all medically qualified personnel ought to have been conversant with this apparently deducible finding.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all the Malawi [30], found that prescribing anti-malaria drugs to only patients that tested positive after parasitological examination of the blood reduced the total number of anti-malaria medicine prescriptions; and by extension the quantity of anti-malaria drugs consumed in a community. Furthermore, introduction of mRDTs in places where malaria diagnosis was usually through presumptive method, demonstrated significant reduction in over prescription of anti-malaria drugs [31]. One would have thought that all medically qualified personnel ought to have been conversant with this apparently deducible finding.…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, RDTs have the potential to improve the case management of febrile illness and slow the development of resistance to ACT by decreasing the number of inappropriate prescriptions (7,8). Additionally, the diagnostic accuracy of RDTs should conceivably motivate recognition and treatment of alternative causes of febrile illness (9) as well as improve the quality of communicable disease surveillance (10).…”
mentioning
confidence: 99%
“…The fact that most people who tested negative on the RDT decided to still take AL also suggests that patients may have lacked confidence in the RDT result. Though our study design is likely to have biased RDT-negative patients toward taking the medicines, several other studies, across different contexts, have also found high prescription and purchase rates of ACTs despite a negative test result, 28,[48][49][50] likely because there is a tendency in malariaendemic areas for both health workers and patients to treat all fever episodes as malaria. [51][52][53] It may be that over time, as patients learn about the accuracy of the test, RDTs will have a greater impact on adherence.…”
Section: Discussionmentioning
confidence: 89%
“…23 Since the symptoms of malaria overlap with several common diseases such as pneumonia, as well as other bacterial and viral infections, [24][25][26] untested patients may face significant uncertainty over whether the illness they are suffering from is malaria, particularly in contexts where they have less confidence in the provider's ability to clinically diagnose the disease. [27][28][29][30] If the practice of stopping medication mid-treatment is related to this uncertainty, then a confirmed malaria diagnosis could encourage patients to complete the treatment.…”
Section: Introductionmentioning
confidence: 99%